Antimicrobial effect and enzymatic activity of extract of Zingiber officinale Roscoe and stability in topical preparations - Gisele Mara Silva Gonçalves; Gustavo Henrique Silva; Pedro Paulo Barros; Silvana Mariana Srebernich; Fernanda Rocha Tonon; Daniella Souza Fiore (São Paulo State University (UNESP), 2014)
The rhizomes of common ginger (Zingiber officinale Roscoe) contain substances with antimicrobial activity and proteolytic enzymes and thus may have various pharmaceutical applications. The aim of the present study was to prepare Zingiber officinale Roscoe rhizome extracts for pharmaceutical use, preserving the proteolytic enzyme activity and testing the antimicrobial activity, in order to develop topical formulations. Two extracts were obtained - aqueous and glycolic - and assessed for their physical, physicochemical and organoleptic characteristics. To measure their proteolytic activity, the extracts were assayed for enzymatic hydrolysis of 1.2% casein solution, at pH 6.0 and 37°C; papain was used for comparison. The antimicrobial activity of the glycolic extract of Zingiber officinale Roscoe was tested by microdilution; the inoculants were prepared from cultures of Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa. There was no growth of S. aureus and S. epidermidis at concentrations of 150 mg/mL or more of extract, whereas P. aeruginosa was inhibited from 100 mg/mL and E.coli from 75 mg/ mL. Emulsion formulations were prepared as vehicles for the extracts and their stability was tested. The results showed proteolytic activity in both Z. officinale rhizome extracts, the glycolic extract having 691.68 PU/g juice and the aqueous extract, 338.14 PU/g juice. The formulations were stable, especially the one that contained the glycolic extract. In sum, the formulations showed satisfactory stability and the Z. officinale extract showed bactericidal activity against the cultures tested; the results are promising for the use of the extract in foods, medicine and cosmetics.